PENELITIAN PERAN SERTA MASYARAKAT DALAM MENGURANGI KERUGIAN AKIBAT KEMACETAN LALU LINTAS DENGAN MENGGUNAKAN TRANSPORT DEMAND MANAGEMENT (TDM) - Agus Bari Sailendra (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Urban traffic congestion is a part of the day-work rutinity, and it tends to spread at wide area, then it becomes strategic issue to concern all society. TDM derives from Transportation System management focused on management demand. One of the approach which TDM used is to manage behaviour road users of urban transportation in using transportation facilities to increase the capacity and operationalisation. The scenario it to observer the behaviour of road user as a public participant. The primary data was collected through structuring interview and supported by related institutions as secondary data. The statistical non-parametric were used on data analysis using three approaches I.e, level of public preferency, participation, and public opinion priority. There is positive indication on society preferency level and there will be policy priority applied in reducing traffic congestions. In general (87%), road user agreed and would participate in running TDM policy. The highest value utility relatively is provided policy alternative on traffic jam billboard information and alternative route (36%), toll/restribution (34%), bus school private or government (32%), and expensive tariff parking-lot (32%). To apply all of them, there should be detailed study, for example, tariff study rising ability to pay (ATP) and willingness to pay (wtp), So, participation of road user in reducing of traffic congestions can be applied optimally